INTEGRATION OF ISLAMIC SCIENCES ACCORDING TO M. AMIN ABDULLAH AND ITS IMPLICATIONS FOR ISLAMIC UNIVERSITIES - Ayu, Adinda; Permatasari, Devi; Maulida, Haliza Salma (Jurnal Asy-Syukriyyah, 2024)
This research aimed to describe the integration of Islamic sciences according to Prof. M. Amin Abdullah and its implications for Islamic universities. The research methods used were library research and bibliographic research. According to Amin, the integration of Islamic knowledge was an essential issue in the development of Islamic knowledge in Indonesia, especially in Islamic religious universities. Amin's reflections emphasized the need for an integrated and interconnected approach to Islamic science, which until now was still fragmented and disconnected from contemporary issues. Amin's theory was based on the classification of Islamic knowledge into four categories: al Qur'an, Sunnah, 'Ulum al Din, al-Fikr al Islamy, and Dirasah al Islamiyyah. These categories corresponded to the concept of a four-layer spider's web, which combined all social and religious principles to solve contemporary problems.